A simple index to adjust maximal strength measures by body mass - Vanderburg, P. M. (Journal of Exercise Physiology online, 1999)
Numerous recent studies have suggested that maximal strength lifts (S) can be adjusted by body mass (M) using the following expression based on allometric scaling (AS): S·M-2/3, thus facilitating appropriate comparisons of strength between individuals of different size. However, use of this convention has not been readily embraced, probably because of the cumbersome nature of calculating with exponents and the strange units or "currency" that results. To provide a more "user friendly" method of adjusting maximal lifts by M, a mathematical transformation of the function associated with the S·M-2/3 index was used to create a simple table for each gender that easily facilitates comparisons. For example, two men, A and B, with S values of 75 and 65 kg, respectively, and M values of 67 and 52 kg, respectively, can be compared to each other by multiplying the index, I, based on M (0.9083 for A and 1.0755 for B) by S. The resulting scores, Sadj, 79.41 kg for A and 81.50 kg for B, are body-mass adjusted indices of S. Therefore, Man B is considered to have a larger body-mass-adjusted S. This index has two advantages over traditional AS methods. First, no exponents are used, thus facilitating easier calculations. Second, the resulting units of Sadj, "kg," are still the same as were those of S, contributing to a more meaningful interpretation. We recommend the use of such a table when individual comparisons of body-mass adjusted strength for men or women is warranted.